Local approaches for the fracture assessment of notched components: the research work developed by Professor Paolo Lazzarin (Fracture and Structural Integrity, 2015)
Brittle failure of components weakened by cracks or sharp and blunt V-notches is a topic of activeand continuous research. It is attractive for all researchers who face the problem of fracture of materials underdifferent loading conditions and deals with a large number of applications in different engineering fields, notonly with the mechanical one. This topic is significant in all the cases where intrinsic defects of the material orgeometrical discontinuities give rise to localized stress concentration which, in brittle materials, may generate acrack leading to catastrophic failure or to a shortening of the assessed structural life. Whereas cracks are viewedas unpleasant entities in most engineering materials, U- and V-notches of different acuities are sometimesdeliberately introduced in design and manufacturing of structural components.Dealing with brittle failure of notched components and summarising some recent experimental results reportedin the literature, the main aim of the present contribution is to present a review of the research work developedby Professor Paolo Lazzarin. The approach based on the volume strain energy density (SED), which has beenrecently applied to assess the brittle failure of a large number of materials. The main features of the SEDapproach are outlined in the paper and its peculiarities and advantages accurately underlined. Some examples ofapplications are reported, as well. The present contribution is based on the author’s experience over about 15years and the contents of his personal library. This work is in honor and memory of Prof. Paolo Lazzarin whosuddenly passed away in September 2014.
Keywords: Notch stress intensity factors